2018
DOI: 10.4314/wsa.v44i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the water use and hydraulic properties of riparian tree invasions: A case study of Populus canescens in South Africa

Abstract: Invasive alien plants (IAPs) pose a serious threat to the already limited water resources in dry countries like South Africa which are facing increasing water shortages. Much of South Africa is expected to get drier in future due to climate change. In addition, the future climatic conditions are also predicted to accelerate the rate at which IAPs will spread, due to favourable growing conditions, further disrupting the provision of goods and services. Previous studies on tree water use in South Africa focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…For windbreaking and decorative purposes, poplar species including P. simonii, P. fremontii, and P. canadensis are planted in homes and streets and are carefully tended to with frequent irrigation. Overall, the results are consistent with Ntshidi et al (2018) and Mtengwana et al (2021), because, from a geographic perspective, invasive species predominate in the wetter parts of the country, which are important water sources for the country's major rivers. Poplar needs enough water and warmer temperatures for better growth and survival (Fischer et al 2018;Kalcsits, Silim & Tanino 2009).…”
Section: Discussionsupporting
confidence: 75%
“…For windbreaking and decorative purposes, poplar species including P. simonii, P. fremontii, and P. canadensis are planted in homes and streets and are carefully tended to with frequent irrigation. Overall, the results are consistent with Ntshidi et al (2018) and Mtengwana et al (2021), because, from a geographic perspective, invasive species predominate in the wetter parts of the country, which are important water sources for the country's major rivers. Poplar needs enough water and warmer temperatures for better growth and survival (Fischer et al 2018;Kalcsits, Silim & Tanino 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Groundwater resources are also reduced in arid areas because some alien tree species draw water from aquifers at a rate in excess of replenishment (Dzikiti et al 2013). In the case of alien deciduous trees, studies have indicated substantially lower increases in evapotranspiration of around 20 mm/yr (Ntshidi et al 2018).…”
Section: Brief Synopsis Of the Prominent Impacts Of Invasive Alien Sp...mentioning
confidence: 99%
“…The impact of specific invasive alien tree species on streamflow has been assessed in field studies, some of which covered extended periods (Table 15.1). These include Acacia mearnsii (Dye and Jarmain 2004;Clulow et al 2011;Everson et al 2014), Eucalyptus camaldulensis (River Red Gum) (Dzikiti et al 2016), Pinus radiata (Monterey Pine) (Dzikiti et al 2013b), Prosopis species (Dzikiti et al 2013a(Dzikiti et al , 2017 and Populus canescens (Grey poplars) (Ntshidi et al 2018). In recent years some studies have also focused on the impacts of the invasive alien plants on groundwater [e.g.…”
Section: Species and Stand-level Studiesmentioning
confidence: 99%